Factibilidad económica de los programas de intervención ergonómica del factor seguridad, carga y diseño físico en el área de Pecuaria, Espam-MFL - Díaz Encarnación, Jessica Viviana (2015)
This research presents the analysis of the economic feasibility of the intervention program including ergonomic factors in the security, load and physical design of units for teaching, research and links to the career of Animal Science in the ESPAM-MFL, starting with a literature review and the application of two phases of the procedure with the techniques of observation and the realization of a check list that identified and described the current situation of workers, such as: direct contact with chemical substances in laboratories and agricultural activities, limits in the physical design of the incubator and the use of incorrect positions in the field units, it was later estimated the magnitude of the risk in the workplace where experts were allocated to the problems encountered, then we used the method of coefficient of Kendall and proceeded with the Matrix Method, using a cartesian plane indicated that the majority of the risk factors needed improvement actions, described the situation in situ, the benefits and the corrective procedure for the improvement actions. It is concluded that it is economically feasible the application of this improvement plan because costs was estimated at $7,893.95 representing 1% of the investment allocated to the unit, it is recommended the application of this improvement plan to have a higher performance, and increases the quality of working life in the organization.